Widely targeted metabolomics reveals the different metabolic changes in leaves and roots of two cotton varieties under drought stress. (27th June 2021) - Zhang, Xiaomeng; Chen, Jing; Feng, Keyun; Wang, Ning; Zhang, Siping; Ma, Huijuan; Ge, Changwei; Shen, Qian; Liu, Ruihua; Zhao, Xinhua; Liu, Shaodong; Du, Xiongming; et al.
Abstract: Cotton yield is affected by drought stress. We performed widely targeted metabolomics to explore metabolic changes under drought stress in the roots and leaves of two cotton varieties differing in drought tolerance—XLZ8 as sensitive and G95079 as tolerant variety. A total of 537 metabolites were detected at different stages of drought stress. Abscisic acid (ABA) was significantly enriched in all stages of drought stress in both roots and leaves of XLZ8. Amino acids showed enrichment in leaves of G95079 in the early stage of drought stress. Flavonoids were significantly enriched in the leaves of the two varieties in the late stage of drought stress. In roots, nucleotides and their derivatives were highly enriched in XLZ8 in the late stage of drought stress. The biosynthetic pathways of kynurenine and polyamine and glycerophospholipid metabolism may play an important role in cotton drought tolerance by scavenging reactive oxygen species (ROS) and reconstructing cell membranes. Spraying appropriate concentrations of proline, kynurenine, S‐adenosylmethionine, glucose and 1‐oleoyl‐2‐hydroxy‐sn‐glycero‐3‐phosphocholine (lyso PC18:1) significantly increased the survival rate of cotton seedlings under drought stress. We speculated that ABA‐dependent and ABA‐independent metabolic changes may lead to differences in drought tolerance among cotton varieties.